Biographic Parallels as a Basis for Typological Studying of George Orwell and Ivan Bahrianyi Works - Svitlana Korshunova; Svitlana Kobuta (Pitannâ Lìteraturoznavstva)
This article deals with the problem of biographic parallelism as a basis for typological research. The main task is to find out similarities and differences in the works by George Orwell and Ivan Bahrianyi, all of them being based of the real facts from the writers' lives. The peculiarities of the literary interpretation of the biography of the both authors become the comparative basis for revealing of the common processes in their works. The research sheds the light on the interdependence between authors' motivations and its literary results. It also highlights the problem of genres chosen by the writers and of the dependence of this choice on the biographic facts usage. The article compares the genres of the authors' works from the point of view of their artistic motivation. The subject under study includes such books of the authors as “Burmese Days”, “Keep the Aspidistra Flying” and other by George Orwell, as well as “The Getsyman Garden”, “The Hunters and the Hunted” and others by Ivan Bahrianyi. It deals with the problem of the influence of the writers' biographic facts on their creation of the literary images and characters, as well as on the plots of the stories. The similarities between authors and their characters are revealed and this allows us to say that writers used their own lives as a source of inspiration and artistic motivation for the sake of making their stories credible. The article also raises the question of the nature of the writers' characters with authors' being their possible prototypes. In general, the article studies the parallels of George Orwell and Ivan Bahrianyi lives, trying to prove their compatibility in the typological field while both use their biographies as a creative method.